2013
DOI: 10.1039/c3nr01145c
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of self-catalytic GaAs:Mn nanowires grown by molecular beam epitaxy on silicon substrates

Abstract: Mn-doped GaAs nanowires were grown in the self-catalytic growth mode on the oxidized Si(100) surface by molecular beam epitaxy and characterized by scanning and transmission electron microscopy, Raman scattering, photoluminescence, cathodoluminescence, and electron transport measurements. The transmission electron microscopy studies evidenced the substantial accumulation of Mn inside the catalyzing Ga droplets on the top of the nanowires. Optical and transport measurements revealed that the limit of the Mn con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 63 publications
(116 reference statements)
2
26
0
Order By: Relevance
“…The LO mode is indeed frequently observed in GaAs NWs under these conditions. 21 Therefore, the absence of the GaAs-like, (In,Ga)As LO mode in Raman spectra further confirms the outstanding quality of the cores of the investigated NWs.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The LO mode is indeed frequently observed in GaAs NWs under these conditions. 21 Therefore, the absence of the GaAs-like, (In,Ga)As LO mode in Raman spectra further confirms the outstanding quality of the cores of the investigated NWs.…”
supporting
confidence: 61%
“…GaAs NWs grow best at high temperatures (550 °C -650 °C), thus first we have investigated the Mn doping limits of GaAs NWs grown in this high temperature range. 21 We have observed that Mn doesn't deteriorate the growth of GaAs NWs, even with quite high Mn/Ga flux ratio of about 3%. We have found that at high growth temperatures, Mn can be introduced into GaAs NWs only at doping levels (below 10 18 cm -3 ).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface. However, due to high disorder in terms of NW orientation, crystallographic defects, and morphology, other growth regimes of Mn-doped GaAs NWs have been exploited: (i) Ga catalyzed NWs grown at high temperature on Si(100), 13 (ii) Ga catalyzed NWs grown at high temperature on Si(111), 22 and (iii) low-temperature grown GaMnAs shells on high-temperature grown Au-catalyzed GaAs NWs on GaAs(111)B. 21 In this paper, we focus on investigating in details structural and compositional properties of Mn-doped Ga catalyzed GaAs NWs grown on Si(111) at high a)…”
Section: Introductionmentioning
confidence: 99%